PEMIKIRAN POLITIK HASAN AL-BANNA (1906 – 1949) DAN PEMBENTUKAN RADIKALISME ISLAM - Otoman Otoman (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2015)
Al-Banna said: "We will not sit back and feel happy or stopped while the Qur'an has not really become institutionalization of the country. We will live to achieve this goal or die from it". In political thought, Hasan al-Banna linking faith with political activity. Surely a Muslim is not perfect keislamanya unless he became a politician, who had the foresight and give full attention to the issue of race. In his view, the Islamic one should lead to give attention to the problems of the nation. Islam is a comprehensive system, covering all aspects of life. Then it is the state and the homeland or the government, people, moral, strength, or compassion and fairness, insight and law, or science and law, material and natural wealth or income and wealth, as well as jihad and da'wa or troops and thought. As well as he is pure and true faith, no less no more. The scope of Islam itself is not possible not to touch the political sphere and the state. It is also associated with the rule in Islam itself that regulate the affairs that require power as executing.